Tailoring truth : politicizing the past and negotiating memory in East Germany, 1945-1990 - Olsen, Jon Berndt (Studies in contemporary European history, 2017)
By looking at state-sponsored memory projects, such as memorials, commemorations, and historical museums, this book reveals that the East German communist regime obsessively monitored and attempted to control public representations of the past to legitimize its rule. It demonstrates that the regime's approach to memory politics was not stagnant, but rather evolved over time to meet different demands and potential threats to its legitimacy. Ultimately the party found it increasingly difficult to control the public portrayal of the past, and some dissidents were able to turn the party's memory politics against the state to challenge its claims of moral authority.